"An Analytical Study for Urban Gentrification on Local Urban Centers" - Mokhles Ibrahim, Noor; ehsan shok, Mufeed (Journal of Planner and Development, 2020)
The urban Gentrification  is an inclusive global phenomenon to restructure the cities on the overall levels, the research to propose a specific study about the concept of urban Gentrification in the cities and showcasing its, specifications, and results, and how to deal with the variables that occur on cities through improvements as part of urban renewal projects, then the general axis of the research is shrinked, choosing the urban centers as the most important areas that deal with the urban Gentrification process due to its direct connection with indivisuals and social changes, and to process the specific axis of the research theses and studies will be showcased that discuss the topic in different research directions, and emerged the research problem in “Lack of comprehensive knowledge regarding the importance of urban Gentrification in developing the urban city centers in general and the speciality of local needs specifically”  and the research goal based on that is “Studying and clarifying the urban Gentrification as an integrated process in developing the urban city centers generally and reviving its neighborhoods specifically”, and building a theortical inclusive frame regarding the urban Gentrification concept in urban centers as an integrated process that includes a group of levels, specifications, and mechanisms, the research bases its goals and processing the research problem to a main hypothesis, that is “The urban Gentrification process in urban centers is achieved by achieving its Diffrents Levels, Economic, social, environmental and cultural.” For the purpose of checking the authenticity of the hypothesis the urban center of Al-Battaween have been elected and tested using the method of surveys given to sample of elected people (specialized in the field) and then the positive effects of the urban Gentrification process were detected, and how it effects on a group of visual features and urban activities within the urban centers specifically and within the city in general.